'Implicit' remittances in family relationships: The case of Bangladeshis in Italy and beyond. (2nd August 2021) - Della Puppa, Francesco; Ambrosini, Maurizio
Abstract: In this article – based on 100 in‐depth interviews with divided and reunited Bangladeshi families in Italy, Bangladesh, and London – we discuss how remittances are influenced by gender relations within the family, what social meanings they assume, what family memberships they reinforce, how the intertwining between migration and family cycle affects them. By adopting an intersectional approach, we show how economic transfers are normally sent to the family of the first‐migrant man, although they may assist the emigration of the wife's male relatives: a phenomenon that we call 'implicit remittances'. A second set of results concerns changes over time in remittances and two events of the family cycle are decisive: the family reunification in Italy and the demise of parents in the country of origin. In both cases, remittances are reduced, cease, or are limited to gifts in particular circumstances.